PENGARUH PENGELUARAN KONSUMSI RUMAH TANGGA, INVESTASI SWASTA DAN BELANJA LANGSUNG PEMERINTAH DAERAH TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN LOMBOK TIMUR TAHUN 2001-2017 - Padli, Padli; Hailuddin, Hailuddin; Wahyunadi, Wahyunadi (Universitas Komputer Indonesia, 2020)
This study entitled the effect of household consumption expenditure, private investment and direct regional government expenditure on economic growth in East Lombok Regency in 2001-2017. This study aims to partially and jointly analyze household consumption expenditure, private investment and direct local government expenditure on economic growth in East Lombok Regency and analyze which variables have a dominant influence on economic growth in East Lombok Regency. This research is a type of causal research with quantitative methods using multiple linear regression analysis methods. Source of data is secondary data in the form of time series data, during the period 2001- 2017. The dependent variable in this study is economic growth, household consumption expenditure, private investment and direct regional government expenditure as the independent variable. Regression results show that household consumption expenditure and private investment have no significant effect on economic growth at Î± 5 percent while the local government direct expenditure variable has a significant effect on economic growth at Î± 5 percent. By simultaneous observations of the three variables are statistically significant at alpha 5 percent. Local government direct expenditure variable has a dominant influence on economic growth with a coefficient value of 4.8816 while the smallest effect on economic growth is the variable of household consumption with a coefficient value of 0.1066. Keywords : Household Consumption Expenditures, Private Investment, Local Government Direct Expenditures and Economic Growth